2020
DOI: 10.17576/gema-2020-2001-08
|View full text |Cite
|
Sign up to set email alerts
|

Defying Out-group Impoliteness: An Analysis of Users’ Defensive Strategies in Disputing Online Criticisms

Abstract: Online social networking sites have become an integral platform in the development of relationships among Internet users around the world. The Internet has made connectivity faster and stronger than the old days. However, studies have shown that many have misused this platform to incite hatred and animosity when expressing themselves. Online derogatory expressions include the usage of slurs, pejoratives, hate-speech, flaming, and trolling, among others. The present study aims to analyse defensive strategies em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Discursive strategies are of great importance in online debate, given their potential to influence persuasive arguments [114], impact how users evaluate and respond to content on social media [9,22,27,55] and reveal social identities and perspectives [8,97].…”
Section: Discursive Strategies In Gender Debatementioning
confidence: 99%
See 1 more Smart Citation
“…Discursive strategies are of great importance in online debate, given their potential to influence persuasive arguments [114], impact how users evaluate and respond to content on social media [9,22,27,55] and reveal social identities and perspectives [8,97].…”
Section: Discursive Strategies In Gender Debatementioning
confidence: 99%
“…Conversely, overgeneralization strategy was associated with contrasting perspectives and probably engaged individuals with dissenting opinions, might appealing to out-group members. Although this strategy was possible to provide different viewpoints and challenges biases for other stakeholders in gender-related issues, it might also intensify conflicts such as incivility and misunderstandings [55]. Further research is warranted to investigate gender differences in in-group and out-group gatherings associated with these strategies, including variations in gathering female and male users and group transformations during discussions.…”
Section: From Gender Debate To Discursive Strategiesmentioning
confidence: 99%
“…Similarly, Tracy et al (as cited in Al Kayed and Al-Ghoweri, 2019) contend that criticism entails a negative evaluation of a person or an action for which they are held accountable. Criticism occurs when words or expressions that contain critical remarks are used to criticize (Ismail & Shanmuganathan, 2020).…”
Section: Translationmentioning
confidence: 99%
“…The impoliteness strategy includes the act of making direct criticism. Impoliteness, especially in particular the act of giving direct criticism, is viewed as an insulting action that could result in problems and disagreements (Ismail et al, 2020). Here, the teacher disapproved of the student's question, damaging her positive face or her desire to be liked and approved by others.…”
Section: Students: Hahahamentioning
confidence: 99%
“…The results of the study have shown that the proposed mobile application records a higher accuracy in detecting cyberbully than other available applications. Ismail et al (2020) offers some novel insights into the field of impoliteness by drawing attention to online users' defensive linguistic behaviour in dealing with out-group impoliteness strategies in online communication. Zawawi et al (2021) study show how the interpretations and reactions of Malaysian audiences on LGBT issues in turn provide a preliminary picture of how the effects of media exposure indirectly influence the psychology of individuals.…”
Section: Hate Speech Issues and Concernsmentioning
confidence: 99%